Uma análise do processo de expansão do ensino superior no Brasil : impacto em Sergipe (1995 2005) - Soares, Wagner Barreto (2009)
This his study objectives to describe the distribution of the education in the Brazilian population (particularly in Sergipe), shows its evolution throughout the time and contributes for the comprehention of its importance for the performance of the Brazilian worker in the labor market, that is, verifies if the expansion occurred in recent years in the sergipean Institutions of Superior Teaching (IES) comes tied to its improvement of quality throughout these years. It analyzes the main aspects of the expansion happened in the IES in recent years in Brazil and Sergipe, discoursing on the advance of the private sector from the middle of the 1990 s and highlighting the processes of quantitative growth and institucional differentiation that had been part of the reorganization of the Brazilian superior Teaching. It looks for to highlight one of the central challenges for the Brazilian superior teaching in the current days: the formulation of policies turned to the system totality, able to dialog with the different formats and academic vocations of the institutions that integrate it. It analyzes the educational policies in Collor, Itamar, Fernando Henrique and Lula governments, trying to understand the complex and dynamic relation of the public policies for superior education in this last government, in what it refers to the Projeto Universidade para Todos (ProUni) and its articulation with the policy tax and the financing by the resignation tax. The present text also approaches the financing of the superior education, having as a period of exemplification the beginning of the 1990 s until the present days. Finally, it makes an approach about the quality of the superior teaching. With the analysis of the available data it comes to the conclusion about the recovery of the capacity of growth of the Brazilian education whose verified expansion in the last few decades was largely supported and sponsored by the private segment and the schedule of reforms of the superior education in the analyzed periods is relevant to the macroeconomic policies in what it refers to the reorganization of the production and the reform of the State.